(untitled) (Journal of Philosophy Culture and Political Science, 2019)
In the article the concept of tabarik is analyzed in theological sense and on the basis of traditions and customs of the Kazakh people. The word tabarik, which is reflected in the religious worldview of the Kazakh people, is derived from the notion of tabarruk in Islam. Despite the fact that linguists and historians give different definitions depending on the semantics of the word, the basic idea of it is near to wishing blessing, to waiting for grace. That is, the sacred concept which has been practically used since the time of the Prophet Mohammed as to pray for Allah and to ask for healing, making the blessing and grace of something intermediary is not a novelty for the Kazakh people. As a result of incorrect interpretation of religious doctrines, the Quran and Hadith texts, and unilateral (tendentious) understanding of some of the words and phrases, some individuals and movements have appeared in the history of Islam who have eliminated the notion of tabarik. Nowadays scratches are made on the unity of the Islamic Ummah and the Muslim community is divided for several parts according to the cause that the practice of making tabarik with the things of the Prophet and the good-natured people pushes to the polytheism. In the article, we eliminate the concept of opponents who have made a false analysis of this notion byhermeneutic and historical analysis. Also the interrelation between the notion of tabarruk in Islam which specifies the essence and content of our theme and the notion of tabarik which is widely used in the Kazakh society is described. Thus, the relationship between religion and tradition is showed evidently. Key words: Tabarik, Quran, Hadith, Theology, Polytheism, Religious Cognition